An ignition delay time and kinetic study of 2-methyltetrahydrofuran at high temperatures. (15th December 2016) - Wang, Jingshan; Wang, Xibin; Fan, Xiangshan; Yang, Kangkang; Zhang, Yingjia
Highlights: Ignition delays of 2-methyltetrahydrofuran (2-MTHF) were measured using a shock tube. Two existed models (Mech I and Mech II) were validated. A new model (Mech III) was developed by combining Mech I and AramcoMech_1.3 from NUI. Ignition delays and soot precursors of 2-MTHF were compared with those of 2-methylfuran. Abstract: Kinetic analyses were performed based on the experimental results of ignition delay times of 2-methyltetrahydrofuran (2-MTHF) using shock tube technique at temperatures of 1050–1800 K, equivalence ratios of 0.5–2.0, fuel mole concentrations of 0.25–1.0%, and pressures of 1.2–10 atm. A new kinetic model of 2-MTHF oxidation named Mech III was established according to the analysis of simulation using two published models (Mech I from Ravi Fernandes group and Mech II from Battin-Leclerc group) and the experimental data in this work. Comparison between simulation and experimental data indicated that Mech II shows remarkable under-prediction while Mech I gives a good agreement with ignition delay times under most conditions except for underprediction on fuel-rich mixtures at relative low temperature around 1250 K. Sensitivity analysis indicated that both models underestimated ignition delay times for the reactions of C0 -C4 molecules, so Mech III was formed by introducing such reactions and can demonstrate improved simulation performance under all conditions. Reaction pathway analysis of Mech III showed that 2-MTHF is mainly consumed through fuel decomposition at high temperatures (around 1550 K), and H-atom abstraction reactions at lower temperatures (around 1250 K), respectively. The comparative experimental and kinetic study between 2-MTHF and 2-methylfuran (MF) indicated that 2-MTHF has higher ignition delay times under the same conditions in this work, while the disparity decreases as the temperature increases, and 2-MTHF produces less soot precursors under high temperature conditions.